2013
DOI: 10.11607/jomi.3039
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Osteoblast-Like SaOS-2 Cells to Modified Titanium Surfaces

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…The surface microtopography is a crucial parameter, especially in the dental field, where optimal roughness has been suggested to be around 1.5 m in terms of the S a value [24,25]. This is a size range which may stimulate osteoblast attachment, proliferation and differentiation, resulting in greater bone formation [26]. In the present study, a different magnitude of roughness was evaluated, with S a values of 10 m. This is characteristic of an as-built surface using the EBM technique, where particles 40-100 m in size are the starting material.…”
Section: Discussionmentioning
confidence: 99%
“…The surface microtopography is a crucial parameter, especially in the dental field, where optimal roughness has been suggested to be around 1.5 m in terms of the S a value [24,25]. This is a size range which may stimulate osteoblast attachment, proliferation and differentiation, resulting in greater bone formation [26]. In the present study, a different magnitude of roughness was evaluated, with S a values of 10 m. This is characteristic of an as-built surface using the EBM technique, where particles 40-100 m in size are the starting material.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments are followed by in vivo experiments, in order to verify the findings obtained in vitro, and also to investigate the effects of the material modifications on the whole organism. It was shown that physical surface treatments (such as surface roughness) play a more important role than chemical modifications 30 . Proper implant modification should result in improved bone-implant attachment and increased mechanical resistance after implantation.…”
Section: An Overview Of Titanium Implant Surface Modificationsmentioning
confidence: 99%
“…23,24 Physical treatment is the first possible approach for biomaterial modification. 25,26 Advantages of acid etching include high maneuverability, low cost, and non-toxity. 27 However, studies on acid-processed dentin have focused generally on dental acid corrosion materials rather than altering the characteristics of dentin for application as possible bone substitute material for clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Physical treatment is the first possible approach for biomaterial modification 25 , 26 . Advantages of acid etching include high maneuverability, low cost, and non‐toxity 27 .…”
mentioning
confidence: 99%